Anterior Communicating Artery Aneurysm Uncommon Hemorrhagic Presentation: Case Report - Oberman, Dan Zimelewicz; Rabelo, Nicollas Nunes; Barros, Rafael Rego; Lopes, Othavio; Amorim, Jorge (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Intracranial aneurysm rupture causes subarachnoid hemorrhage in 80% of the cases, and it may be associated with intracerebral hemorrhage and/or intraventricular hemorrhage (IVH) in 34% and 17% of the patients, respectively. However, on rare occasions, aneurysm rupture may be present causing isolate intracerebral hemorrhage or IVH without subarachnoid hemorrhage.We describe an unusual case of an anterior communicating aneurysm rupture presented with IVH, without subarachnoid hemorrhage.Although isolated IVH is rare, aneurysm rupture is a possible condition. Patients presenting with head computed tomography revealing IVH without subarachnoid hemorrhage should be promptly investigated with contrasted image exam to identify and treat possible causes, even in the absence of subarachnoid hemorrhage.
Keywords: aneurysm rupture; anterior communicating aneurysm; intraventricular hemorrhage; subarachnoid hemorrhage